Nutritional state and stages of behaviour change regarding physical activity among children and adolescents from Bogotá, Colombia: The FUPRECOL study (2016)
Objective: This study was related to stages of change in behaviour regarding physical activity and nutritional state in amonq school children in Bogotá, Colombia, who were participating in the FUPRECOL study. Methods: This was a cross-sectional study in which 8.000 9 to 17 year-old children and adolescents participated; they came from 24 educational institutions in Bogotá, Colombia. A self-completed questionnaire regarding behavioural change concerning an intension to engage in physical activity (CCC-FUPRECOL) was completed and weight and stature were measured for determining nutritional state according to body mass index (BMI). Results: There was a 82,5% response and 6,606 replies were considered valid, 58.3% (n = 3,850) being from girls having an average age of 12.7 ± 2.3 years-old. The study population overall was placed in the following stages: 5.3% in the pre-contemplation stage, 31.8% in contemplation, 26.7% in action and 36.2% in the maintenance stage. When change stage was compared to nutritional state by BMI, those schoolchildren classified as being obese had a higher frequency of response regarding the pre-contemplation stage, whilst schoolchildren having a healthy weight had higher rates regarding the maintenance stage. Conclusion: A statistically significant relationship was found for schoolchildren in Bogotá, Colombia, when comparing the intension to engage in physical activity and nutritional state by BMI. Encouraging the promotion of physical activity and monitoring nutritional state must become a priority on public agendas and policies regarding the scholastic setting. © 2016, Grupo Aula Medica S.A. All rights reserved.